Chinese Herbal Medicine on Cardiovascular Diseases and the Mechanisms of Action - Liu, Cuiqing; Huang, Yu (Frontiers in Pharmacology, 2016)
Cardiovascular diseases are the principal cause of death worldwide. The potentially serious adverse effects of therapeutic drugs lead to growing awareness of the role of Chinese herbal medicine in the treatment of cardiovascular diseases. Chinese herbal medicine has been widely used in many countries especially in China from antiquity, however, the mechanisms by which herbal medicine acts in the prevention and treatment of cardiovascular diseases are far from clear. In this review, we briefly describe the characteristics of Chinese herbal medicine by comparing with western medicine. Then we summarize the formulae and herbs/natural products applied in the clinic and animal studies being sorted according to the specific cardiovascular diseases. Most importantly, we elaborate the existing investigations into mechanisms by which herbal compounds act at the cellular levels, including vascular smooth muscle cells, endothelial cells, cardiomyocytes and immune cells. Future research should focus on well-designed clinic trial, in-depth mechanic study, investigations on side effects of herbs and drug interactions. Studies on developing new agents with effectiveness and safety from traditional Chinese medicine is promising for prevention and treatment of patients with cardiovascular diseases.